Atypical variation within the deep gluteal region: A case report featuring double piriformis, non-forming sciatic nerve, and abnormal course of the gluteal vessels - Kara Coffman-Rea; Skylar Arwood; Karen E. Samonds (Elsevier, 2024)
Anatomical variations related to the sciatic nerve and its surrounding structures are well-documented, relevant for certain medical procedures, and identified as contributors to pathological conditions. Variations of the sciatic nerve are often classified by its relative position to the piriformis muscle. However, there are inconsistencies in the description and depiction of these variations, along with instances of atypical variations that do not fall within any specific classification. This case report describes an anatomic abnormality found during a routine cadaver dissection involving the bilateral presence of a double piriformis, absence of sciatic nerve formation (tibial and common fibular nerves never within a shared sheath) and an atypical course of the inferior gluteal vessels perforating the right tibial nerve.